ETNOMATEMATIKA SISTEM BILANGAN MASYARAKAT MANGGARAI - Melkior Wewe; Maria Anjelina Putrini (Jurnal Ilmiah Mandalika Education (MADU), 2024)
Basically, mathematics is an abstract science that has many applications in everyday life. Exploring Manggarai culture in culture and its application in life and its relation to number system material. For this reason, the aim of this research is to study the ethnomathematics of Manggarai culture and number systems. A group of people has a number system that has been developed to represent the quantities of an object. And this number system is applied in everyday life. This type of research is qualitative research with an ethnographic approach. The primary data sources in this research are traditional figures from the Manggarai community and secondary data from journals and literature related to number systems. The data collection method used was unstructured interviews. The results of this research show that the people of Manggarai Regency have ten cardinal numbers, namely numbers one to ten, while the other numbers are the result of developing these cardinal numbers. This number system is applied by the people of Manggarai Regency in naming days. Furthermore, the results of this research can be applied to learning in schools.